2019
DOI: 10.1111/jcmm.14798
|View full text |Cite
|
Sign up to set email alerts
|

N‐acetylcysteine prevents oxidized low‐density lipoprotein‐induced reduction of MG53 and enhances MG53 protective effect on bone marrow stem cells

Abstract: MG53 is an important membrane repair protein and partially protects bone marrow multipotent adult progenitor cells (MAPCs) against oxidized low‐density lipoprotein (ox‐LDL). The present study was to test the hypothesis that the limited protective effect of MG53 on MAPCs was due to ox‐LDL‐induced reduction of MG53. MAPCs were cultured with and without ox‐LDL (0‐20 μg/mL) for up to 48 hours with or without MG53 and antioxidant N‐acetylcysteine (NAC). Serum MG53 level was measured in ox‐LDL‐treated mice with or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“… 6 , 10 , 11 , 35 , 36 We have demonstrated before that MG53’s membrane repair function is impaired when cells are subjected to chronic oxidative stress. 37 , 38 We next conducted a series of studies to quantify the potential protective role of rhMG53 in mitigating NM‐induced oxidative stress and injury to B2B cells. We used DCF fluorescent indicator to quantify intracellular ROS level and observed a significant increase in DCF fluorescence in B2B cells treated with 50 µM NM for 2 h (Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 , 10 , 11 , 35 , 36 We have demonstrated before that MG53’s membrane repair function is impaired when cells are subjected to chronic oxidative stress. 37 , 38 We next conducted a series of studies to quantify the potential protective role of rhMG53 in mitigating NM‐induced oxidative stress and injury to B2B cells. We used DCF fluorescent indicator to quantify intracellular ROS level and observed a significant increase in DCF fluorescence in B2B cells treated with 50 µM NM for 2 h (Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“… 6 , 10 , 11 , 35 , 36 Previously, we have demonstrated that MG53’s membrane repair function is impaired when cells are subjected to chronic oxidative stress. 37 , 38 The preservation of cell integrity and mitigation of oxidative stress can provide added benefits to pulmonary protection. Using cultured lung epithelial (B2B) and endothelial (PAoEC) cells, we found that rhMG53 treatment can improve survival of the cells and reduce ROS levels upon exposure to NM.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 76 AD mice (APP/PS1 transgenic mice, 6-month old) were divided into different groups and C57BL/6 mice were used as WT control. For in vivo anti-aging study, 16 AD mice were respectively intravenously administered 0.9% saline, P5 hUC-MSCs (P5), P15 hUC-MSCs (P15) and MG53 pretreated P15 hUC-MSCs (MG53-P15) as previously reported [ 16 ]. In order to investigate the effects of combined therapy, 44 AD mice were divided into 4 groups: AD (AD mice injected with vehicle), MG53, MSCs, and MG53+MSCs.…”
Section: Methodsmentioning
confidence: 99%
“…Mitsugumin53 protein (MG53), known as TRIM72, has protective effects on muscle, lung, kidney, brain, and other cells or tissues [ [12] , [13] , [14] , [15] ]. It was reported that recombinant human MG53 protein (rhMG53) could protect bone marrow mesenchymal stem cells from low density lipoprotein-induced membrane damage [ 16 ]. Our previous work proved that rhMG53 could enhance the anti-oxidative and anti-inflammatory capacity of hUC-MSCs and promote the functional recovery of brain injury [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…After dialysis using 5 µM copper sulphate at 4˚C overnight, ox-LDL was sampled from the native LDL immediately, as previously described ( 26 ). Thiobarbituric acid reactive substances (TBARS; Sigma-Aldrich; Merck KGaA) were used to monitor the degree of LDL oxidation and to ensure ox-LDL quality and reproducibility using a microplate reader at a wavelength of 532 nm (BioTek Instruments, Inc.) ( 27 ). Specifically, the TBARS value was maintained at 40-50 nmol malondialdehyde/mg protein.…”
Section: Methodsmentioning
confidence: 99%